Manf Enhances the Pyroptosis Inhibition of Bone Marrow-derived Mesenchymal Stem Cells to Relieve Cerebral Infarction Injury. (1st February 2023) - Zhang, Qi; Shi, Shanshan; Tang, Yushi; Qu, Changda; Wen, Shirong; Pan, Yujun
Graphical abstract: Highlights: Pyroptosis-related genes upregulate in brain cell clusters concurrently after MCAO. MANF inhibits pyroptosis. Manf -modified BMSCs play a strong therapeutic role in cerebral infarction. Abstract: Cerebral infarction is a common disease characterized by high mortality, a narrow therapeutic window, and limited therapeutic options. Recently, cell therapy based on gene modification has brought a glimmer of hope to the treatment of cerebral infarction although the explicit underlying mechanism is beyond being well dissected. In the present study, we constructed an animal model of middle cerebral artery occlusion (MCAO), compared differentially expressed genes (DEGs) between the sham and MCAO groups by single-cell RNA sequencing (scRNA-seq) to explore the potential cell death-related pathways involved in cerebral infarction, and transfected Manf into BMSCs by lentivirus. Subsequently, we injected BMSCs (bone marrow-derived mesenchymal stem cells), Manf -modified BMSCs, or lentivirus encoding Manf into the brain. Their effects on MANF content, apoptosis, pyroptosis, infarct volume in the brain, and neurological function were evaluated after MCAO. We found that the DEGs upregulated in four major cell clusters after MCAO and were enriched with not only apoptosis, ferroptosis, and necroptosis but also with pyroptosis-related pathways. In addition, transfection of Manf into BMSCs significantly increased the expression and secretion of MANF in BMSCs; BMSCs, Manf -modified BMSCs, and Manf treatment all resulted in an increase in Manf content in the brain, a decrease in the expression of apoptosis- and pyroptosis-related molecules, a reduction in infarct volume, and an improvement in neurological function after MCAO. Moreover, Manf -modified BMSCs have the strongest therapeutic effect. Collectively, Manf -modified BMSCs ameliorate ischemic injury after cerebral infarction by repressing apoptosis- and pyroptosis-related molecules, which represents a new cell therapy strategy for cerebral infarction.